THE LEXICON VARIATIONS OF RONGGA AND WAERANA LANGUAGE IN EAST MANGGARAI NUSA TENGGARA - Erliana Eni Tuwa (EL2J (English Language and Literature Journal), 2022)
This research aims to describe the variations of the Rongga language inEast Manggarai, Nusa Tenggara. In this study, found the words in whichused by the Rongga community. They have differences and similarities inspeech, but Rongga language has the same meaning with Waeranalanguage. This occurrence because the location of the both areas is nearso that vocabulary appeared based on different areas in the field lexicon.The research method used in this research is descriptive qualitativemethod and data collection methods using interviews with transcripts andrecording techniques. This research used the theory of dialectology todescribe the variation of Rongga and Waerana language. In this research,found 35 variations of lexicons Rongga and Waerana words.there are 10word verbs, 8 word adjectives, 10 words nouns, 7 words personalpronouns. Therefore, it is very clear that geographical conditions andsocial dialect factors effecting language variations that develop in eachregion.